The Impact of Good Corporate Governance Implementation on Firm Value - Ekasari, Juendiny Chrisna; Kus Noegroho, Yefta Andi (Universitas Pendidikan Ganesha, 2020)
Many banking companies that offer shares on the Indonesia Stock Exchange, so it is very important for banking companies to pay attention to the value of their companies. This study aims to analyze the effect of the implementation of Good Corporate Governance on firm value through the existence of profitability. This study used a quantitative approach and secondary data collection, by testing the causal relationship of measurable research variables, namely examining the effect of GCG on firm value and profitability and positioning the profitability variable as an intervening variable. This study found that the direct relationship between GCG and profitability to firm value has an influence. Whereas, the results of this study also indicate the ineffective use of the proxied profitability of Return on Equity (ROE) as an intervening variable in the effect of GCG on firm value. This means that in banking companies listed on the IDX for the 2017-2019 period, GCG does not have an indirect effect on company value through profitability. Based on the results, if bank management pays more attention to the application of the principles of good governance (GCG), it will have an impact on increasing firm value.